2022
DOI: 10.1186/s12964-022-00952-x
|View full text |Cite
|
Sign up to set email alerts
|

MICAL2 contributes to gastric cancer cell migration via Cdc42-dependent activation of E-cadherin/β-catenin signaling pathway

Abstract: Background Gastric cancer is a common and lethal human malignancy worldwide and cancer cell metastasis is the leading cause of cancer-related mortality. MICAL2, a flavoprotein monooxygenase, is an important regulator of epithelial-to-mesenchymal transition. The aim of this study was to explore the effects of MICAL2 on gastric cancer cell migration and determine the underlying molecular mechanisms. Methods Cell migration was examined by wound healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…β-catenin, or CTNNB1, is an evolutionarily conserved, multifunctional intracellular protein. β-catenin was originally identified in cell adhesion junctions (AJs), where it functions to link the cytoplasmic domains of cadherins to the a-catenin and actin cytoskeletons in response to cell-cell adhesion(Nakayama et al , 2014; Puthia et al , 2014; Wang et al , 2022). CDH1 and β- catenin form a complex in cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…β-catenin, or CTNNB1, is an evolutionarily conserved, multifunctional intracellular protein. β-catenin was originally identified in cell adhesion junctions (AJs), where it functions to link the cytoplasmic domains of cadherins to the a-catenin and actin cytoskeletons in response to cell-cell adhesion(Nakayama et al , 2014; Puthia et al , 2014; Wang et al , 2022). CDH1 and β- catenin form a complex in cells.…”
Section: Resultsmentioning
confidence: 99%
“…CDH1 and β- catenin form a complex in cells. This complex is a critical component of the cell-cell adhesion complex(Wang et al , 2022; Liu et al , 2022; Jovov et al , 2011). Thus, in this work, K14 was measured as a biomarker of HaCaT cells, while CDH1, β-catenin, and ZO-1 were measured as functional biomarkers of cell-cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, MICAL2 has been identified as a novel pro-tumorigenic factor 39 . Previous studies have indicated that, in addition to being highly expressed in cancers, MICAL2 is associated with poor prognosis 23 , 24 , 40 , 41 . In our study, we found that MICAL2 was highly expressed in pancreatic cancer samples.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, MICAL2 has been found to be highly expressed in many tumors and promote tumor progression by inducing tumor cell proliferation and migration 19 22 . In gastric cancer, MICAL2 has been shown to promote gastric cell migration by disrupting the impaired binding of E-cadherin to β-catenin, resulting in the accumulation of β-catenin in the nucleus, which enhances β-catenin signaling 23 . High expression of MICAL2 is associated with poor prognosis for glioblastoma patients, as well as the promotion of glioblastoma in mice 24 .…”
Section: Introductionmentioning
confidence: 99%
“…MICAL family members are associated with cytoskeletal remodeling and cell migration (Table ), 43 which can result in invasion and metastasis 44 . MICAL2 is reportedly overexpressed in various tumors, including gastric cancer 45 and lung cancer 46 . Moreover, silencing of MICAL2 promotes mesenchymal to epithelial transition, and inhibits the viability, as well as the motility and invasive properties, of human cancer cells 47 .…”
Section: Discussionmentioning
confidence: 99%